Cancer-associated Retinopathy Developing After 10 Years of Complete Breast Cancer Remission. (2nd January 2019) - Igarashi, Nozomi; Sawamura, Hiromasa; Kaburaki, Toshikatsu; Aihara, Makoto
ABSTRACT: A 73-year-old female with a past medical history of breast cancer, who 10 years earlier experienced complete remission, complained of bilateral visual field disturbances and photopsia, 2 months prior. Tumour recurrence and metastatic lesions were not found during the medical examination, but antibodies against recoverin were detected in her serum. Despite immunosuppressive treatment with prednisolone and plasmapheresis, rapid and diffuse degeneration of the patient's photoreceptors and deterioration of her visual field were observed. This is a rare case of cancer-associated retinopathy with a long interval (10 years) between the diagnosis of the malignancy and visual loss.